Utilizing a Minimum of Four Antenatal Care Visits and Associated Factors in Debre Berhan Town, North Shewa, Amhara, Ethiopia, 2020 - Tizazu MA; Asefa EY; Muluneh MA; Haile AB (Dove Medical Press, 2020)
Michael Amera Tizazu, Eyosiyas Yeshialem Asefa, Mikyas Arega Muluneh, Asalif Beyene Haile Department of Midwifery, Health Science College, Debre Berhan University, Debre Berhan, EthiopiaCorrespondence: Eyosiyas Yeshialem AsefaDepartment of Midwifery, Health Science College, Debre Berhan University, Debre Berhan, EthiopiaTel +251 913836869Email eyosi143@gmail.comBackground: Receiving a minimum of four antenatal care, as per the World Health Organization recommendation, enhances the possibility of utilizing effective maternal health care during antenatal follow-up. Hence, this study aimed to identify the level of a minimum of 4 ANC usage and factors associated with Debre Berhan town.Methods: A community-based cross-sectional study was employed from February 20 to March 10/2020 among women who gave birth in the last 6 months before the data collection period in Debre Berhan town. Data were collected using face-to-face interviews with the pre-tested tool by trained data collectors from randomly selected participants. After entering the data into Epi-data software version 3.1, it was further processed using SPSS version 23 statistical package. Both bivariate and multivariable Logistic regressions were fitted to identify the determinants for the utilization of a minimum of 4 antenatal care. A significance level of 0.05 was used to decide the significance of statistical tests.Results: A total of 390 women were interviewed giving a response rate of 99.2%. In this study, 78.5% (95% CI: 74.4– 82.6) of women received a minimum of four antenatal care visits. Maternal educational status, initiation of antenatal visit at ≤ 16 weeks of gestation, and husband support/partner involvement were identified predictors of utilization of minimum 4 antenatal visits.Conclusion and Recommendations: Use of at least four antenatal visits in Debre Berhan town was found to be good. Health promotion programs targeting mothers with no education and lower educational level are important to increase their awareness about the importance of antenatal services. Male partner involvement during care related to pregnancy and promoting early initiation of antenatal care is important to overcome challenges towards a minimum of 4 antenatal visits in Debre Berhan town.Keywords: minimum four antenatal, utilization, Ethiopia